Living with the earth : - Moore, Gary S. (CRC Press, 2007)
With an emphasis on biological, chemical, and physical sources of pollution, this book incorporates traditional concepts of environmental health with new controversies regarding environmental threats to human health, such as the link between air pollutants and asthma as well as the role of pollution in cancer risk. This edition also features new chapters on emerging diseases and emergency preparedness, including the significant reasons for the emergence of these diseases and the main etiological agents related to them. The text balances its presentation by offering opposing views of major issues, ranging from the Greenhouse Effect to reproductive problems associated with endocrine disruptors.